Synthesis of ALD Tungsten Trioxide Thin Films from W(CO)6 and H2O Precursors. (10th September 2015) - Zhang, Kai; McCleese, Christopher; Lin, Pengtao; Chen, Xin; Morales, Monica; Cao, Wei; Seo, Felix J.; Burda, Clemens; Baumgart, Helmut
Abstract : Tungsten oxide (WO3) was successfully deposited by atomic layer deposition (ALD) usingtungsten hexacarbonyl [W(CO)6] and DI water [H2O]. A saturated growth rate is of 0.2 Å perALD cycle was determined at a growth temperature of 300 °C. The as-deposited ALD WO3 filmswere found to be amorphous, which was corroborated by X-ray diffraction. Post-depositionthermal annealing at an elevated temperature transformed the WO3 phase to a monoclinic crystalstructure. The optical measurement confirmed that the ALD WO3 thin film possessed a band-gapof 3.28 eV.